Contamination detection — new calls - Władysław Harmata (Biuletyn Wojskowej Akademii Technicznej, 2022)
The overview article deals with the current issue of contamination detection. Unfortunately,the threat of the possibility of using weapons of mass destruction in a local conflict caused byRussia cannot be excluded. In addition, analysing contemporary threats, it is necessary to take intoaccount the possibility of activity of terrorists using improvised explosive devices with acetone andurotropin peroxides. The country’s contamination reconnaissance (detection) system is technicallyand procedurally outdated compared to NATO solutions. Point detectors and patrols operating in thearea of contamination domi-nate, while in NATO armies remote systems, e.g., using lidar techniques,unmanned means, etc., are used. Poland has all the elements to establish this type of contaminationreconnaissance system.Keywords: chemical sciences, improvised explosive devices, detection and monitoring of contamination.